2010
DOI: 10.1007/s10620-010-1157-x
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Induces Apoptosis In Vitro and Slows Growth of Tumor Xenografts but Not Polyp Formation in Min Mice

Abstract: Atorvastatin can induce apoptosis in vitro, through mevalonate and prenylation pathways. Atorvastatin, while not effective in preventing polyp formation in the min mouse model, was very effective in slowing tumor growth in a nude mouse model. Consistent with in vitro findings, increased apoptosis accounted for decreased tumor growth. Statins may have benefit in cancer by slowing tumor growth, rather than preventing tumor initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Total cellular lysates were subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) as previously described. 13 aSMA protein was detected with a mouse monoclonal antibody to human aSMA protein (Sigma). GAPDH protein expression was used as a loading control using a mouse antibody to GAPDH (Chemicon, Temecula, CA).…”
Section: Protein Expressionmentioning
confidence: 99%
“…Total cellular lysates were subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) as previously described. 13 aSMA protein was detected with a mouse monoclonal antibody to human aSMA protein (Sigma). GAPDH protein expression was used as a loading control using a mouse antibody to GAPDH (Chemicon, Temecula, CA).…”
Section: Protein Expressionmentioning
confidence: 99%
“…Various statins, which inhibit cholesterol synthesis by blocking activity of 3-hydroxy-3-methylglutaryl CoA reductase (HMG-CoAR), have been shown to reduce tumor growth in xenograft models (Gao et al, 2010; Huang et al, 2010; Kochuparambil et al, 2011). Moreover, pharmacological inhibition of squalene synthase, the first committed step in cholesterol synthesis, lowered resistance to the chemotherapeutic agent doxorubicin in a xenograft model of liver cancer, albeit without significant effect on tumor growth, when used on its own (Montero et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Statins are competitive small-molecule inhibitors of HMG-CoA reductase, and could prevent the transformation of HMG-CoA to mevalonate (24). Although in vitro data have suggested that ATST could suppress HCT116 cell growth and induce apoptosis, the effective doses of ATST in these experiments were relatively higher (50 and 100 µM, respectively) (12,25). In our experimental design, the maximum dose of ATST was only 25 µM.…”
Section: Discussionmentioning
confidence: 75%